Memory transmission in small groups and large networks: An empirical study - Gates, Vael; Suchow, Jordan W.; Griffiths, Thomas L. (Psychonomic bulletin & review, 2022)
When people try to remember information in a group, they often recall less than if they were recalling alone. This finding is called collaborative inhibition , and has been studied primarily in small groups because of the difficulty of bringing large groups into the laboratory. To study the dynamics of collaborative inhibition in large groups (Luhmann & Rajaram, Psychological Science , 26 , 1909–1917, 2015 ) constructed an agent-based model that extrapolated from previous laboratory experiments with small groups. The model predicts that collaborative inhibition should increase with group size. Here, we evaluate this model by recruiting a large number of participants using crowdsourcing, allowing us to replace the artificial agents in the model with people to study collaborative memory at larger scales. Our empirical results did not match the model predictions: there was no evidence for an increase in collaborative inhibition with group size, despite substantial power to detect such an effect. These findings motivate further empirical work to elucidate the mechanisms of collaborative memory.